Tingkat Kecerdasan, Perilaku Belajar, dan Kompetensi Dosen dalam Peningkatan Pemahaman Akuntansi (Sarana Pendidikan sebagai Pemoderasi) - Siti Nafisah Azis (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2021)
This research examines the effect of the level intelligence (intellectual intelligence, emotional intelligence, and spiritual intelligence), learning behavior, and competence of lecturers on the level of accounting understanding with educational facilities as moderating variable. The research population was all students majoring in accounting at Politeknik Negeri Ujung Pandang. The sample selection used purposive sampling method that generates total sample of 73 students. This research used primary and secondary data were analyzed using moderation regression analysis with the difference absolute value test. The result of this research showed that intellectual intelligence had a negative effect on the level of accounting understanding. Emotional intelligence and learning behavior had a positive effect on the level of accounting understanding. Spiritual intelligence, competence of lecturers, and educational facilities had no effect on the level of accounting understanding. Educational facilities cannot moderate the effect of the level of intelligence, learning behavior, and competence of lecturer on the level of accounting understanding. Indicators of social skills, being flexible, and practical intelligence influence the level of accounting understanding. This research provides new evidence that educational facilities have not been able to make a real contribution in improving students’ understanding of accounting, both as a main and supporting factor. Keywords: level of intelligence; learning behaviour; competence of lecturer; educational facilities; level of accounting understanding